INNOVATION OF ESP DESIGN TO IMPROVE STUDENTS’ ENGLISH LEARNING ACHIEVEMENTS IN NON-ENGLISH DEPARTMENT - Rini Ekayati; Imelda Darmayanti Manurung; Selamat Husni Hasibuan (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2022)
Designing and providing learning materials that suit the needs of learners is one of the important roles of a lecturer. This study is conducted to examine the appropriate English learning design in non-English Education Study Programs at UMSU with an orientation to the English for Specific Purpose (ESP) approach to analyze the factors that become ESP learning needs and analysis of ESP English learning model design in non-English Education Study Programs. This study involved eight lecturer respondents who teach English in non-educational study programs. This study used a qualitative research design using questionnaires and interviews as research instruments. The results of data analysis showed that factors that underlined the need for ESP in teaching and learning English in non-English Education department were going under two categories, namely the short-term factor and the long-term need factor. The design of the ESP English learning model, then, was concerned to the students’ need of English after their study period. This fact is in accordance with the theory of ESP learning approach under the skill-centered course design which aims to help learners develop skills and strategies that will continue after the ESP learning. The combination of both (Learning-centered approach and skill-centered course design) emerged as an innovation of the ESP course design for students of non-English study program.